2016
DOI: 10.1002/adma.201600437
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Coupled Nafion Molecules and Ordered Porous CdS Networks for Enhanced Visible‐Light Photoelectrochemical Hydrogen Evolution

Abstract: Strongly coupled Nafion molecules and ordered porous CdS networks are fabricated for visible-light photoelectrochemical (PEC) hydrogen evolution. The Nafion layer coating shifts the band position of CdS upward and accelerates charge transfer in the photoelectrode/electrolyte interface. It is highly expected that the strong coupling effect between organic and inorganic materials will provide new routes to advance PEC water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
78
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 53 publications
3
78
0
Order By: Relevance
“…

Thereafter, the photocatalytic degrada tion of polychlorobiphenyls [2] and photo electrocatalytic reduction of CO 2 into hydrocarbon compounds [3] in aqueous semiconductor suspensions greatly broad ened the applications of photocatalysis. [4][5][6][7][8][9][10][11] Generally, the photocatalytic reactions can be divided into three basic processes. [4][5][6][7][8][9][10][11] Generally, the photocatalytic reactions can be divided into three basic processes.

…”
mentioning
confidence: 99%
“…

Thereafter, the photocatalytic degrada tion of polychlorobiphenyls [2] and photo electrocatalytic reduction of CO 2 into hydrocarbon compounds [3] in aqueous semiconductor suspensions greatly broad ened the applications of photocatalysis. [4][5][6][7][8][9][10][11] Generally, the photocatalytic reactions can be divided into three basic processes. [4][5][6][7][8][9][10][11] Generally, the photocatalytic reactions can be divided into three basic processes.

…”
mentioning
confidence: 99%
“…Hydrogen generation through the splitting of water by photocatalysis has been considered as a promising solution to the current energy and environmental dilemma 2. In the past decades, various semiconductors, such as TiO 2 ,3 CdS,4 ZnO,5 C 3 N 4 ,6 and WO 3 ,7 were used to water splitting by harnessing solar energy 8. Among these materials, TiO 2 , a kind of semiconductor with a band gap of 3.0–3.2 eV, has been considered as one of promising candidates for photocatalytic H 2 generation owing to its excellent stability and low cost 9…”
Section: Introductionmentioning
confidence: 99%
“…[1][2] The rational design and fabrication of suitable photoanode materials are crucial for achieving efficient PEC water splitting system. [10][11][12][13][14][15][16][17] However, many studies have revealed that the PEC activity of pure CdS is severely limited because of the highly photogenerated carrier recombination. [6][7][8][9] The PEC application of CdS has been intensively studied.…”
Section: Introductionmentioning
confidence: 99%